OP0264-HPR PERSPECTIVES ON APPROACHES TO PREDICT THE DEVELOPMENT OF RHEUMATOID ARTHRITIS: A QUANTITATIVE ASSESSMENT OF PATIENTS AND THEIR FIRST DEGREE RELATIVES. (2nd June 2020) - Wells, I.; Simons, G.; Stack, R.; Mallen, C.; Nightingale, P.; Raza, K.; Falahee, M.
Abstract : Background: There is considerable interest within the medical research community in the identification of individuals at risk of developing rheumatoid arthritis (RA), to identify those who may benefit from preventive interventions. However, it is important to understand the views of those who may be candidates for such predictive tests, to inform the development of effective approaches. First degree relatives (FDRs) of patients with RA are at an increased risk of developing RA. RA patients can provide access to FDRs. Qualitative investigations have explored the views of these groups about predictive testing for RA 1, 2, but quantitative approaches are needed to develop a robust understanding. Objectives: To identify predictors of interest in predictive testing for FDRs and patients, and to assess the likelihood of patients communicating information about RA risk to their FDRs. Methods: Surveys were completed by 482 RA patients and 397 of their FDRs. Patients were invited to complete the survey and to provide another to their relatives. Spearman's Rank Correlations were used to assess relationships between interest in predictive testing/ likelihood of risk communication and potential predictor variables. Results: FDRs had a median age of 41 years, 64% were female. 57% were definitely interested and 36% were probably interested in taking a predictive test for RA. Several predictors were found to be associated with interest (table 1 ). Patients had a median age of 65 years, 71% were female. 47% were definitely interested and 30% were probably interested in their children taking a predictive test. Several predictors were found to be associated with interest (table 1 ). On a Likert scale from extremely unlikely (0) to extremely likely (4), most patients indicated that they were likely to communicate RA risk information to their children (median score=3). Conclusion: Interest in predictive testing for RA was high amongst FDRs, and factors including information seeking preference, RA risk perception, concern about RA, perceived consequences of RA and health anxiety were significantly associated with interest. Patients were also willing to communicate information about RA risk to their children. These findings increase understanding of perceptual variation in those at risk of RA, and will inform the development of information to support decision making in individuals considering predictive tests and preventive interventions. We are currently extending this preliminary analysis by building multivariate models incorporating a range of attitudes about predictive testing, assessing predictors of patients' likelihood of communicating to their FDRs about risk, and the relationship between patients' and FDRs' responses. References: [1]Stack RJ et al. BMJ open. 2016; 6(6):e010555. [2]Falahee M et al. Arthritis care & research. 2017; 69(10):1558-65. Acknowledgments: This work was supported by Versus Arthritis; Grant reference: 21560. Disclosure of Interests: Imogen Wells: None declared, Gwenda Simons: None declared, Rebecca Stack: None declared, Christian Mallen Grant/research support from: My department has received financial grants from BMS for a cardiology trial., Peter Nightingale: None declared, Karim Raza Grant/research support from: KR has received research funding from AbbVie and Pfizer, Consultant of: KR has received honoraria and/or consultancy fees from AbbVie, Sanofi, Lilly, Bristol-Myers Squibb, UCB, Pfizer, Janssen and Roche Chugai, Speakers bureau: KR has received honoraria and/or consultancy fees from AbbVie, Sanofi, Lilly, Bristol-Myers Squibb, UCB, Pfizer, Janssen and Roche Chugai, M. Falahee: None declared